Using all our genomes: Blood‐based liquid biopsies for the early detection of cancer. Issue 1 (31st January 2022) - Adams, Eddie; Sepich‐Poore, Gregory D.; Miller‐Montgomery, Sandrine; Knight, Rob
Abstract: The pursuit of highly sensitive and specific cancer diagnostics based on cell‐free nucleic acids isolated from minimally invasive liquid biopsies has been an area of intense research and commercial effort for at least two decades. Most of these tests detect cancer‐specific mutations or epigenetic modifications on circulating DNA derived from tumor cells (ctDNA). Although recent FDA approvals of both single and multianalyte liquid biopsy companion diagnostic assays are proof of the tremendous progress made in this domain, using ctDNA for the diagnosis of early‐stage (stage I/II) cancers remains challenging due to several factors such as low mutational allele frequency in circulation, overlapping profiles in genomic alterations among diverse cancers, and clonal hematopoiesis. This review discusses these analytical challenges, interim solutions, and the opportunity to complement ctDNA diagnostics with microbiome‐aware analyses that may mitigate several existing ctDNA assay limitations. Abstract : Genomic and metagenomic features for minimally invasive, blood‐based detection of cancers . Here, we discuss established and emerging methods of analyzing and diagnosing cancers through blood‐based noninvasive liquid biopsy assays with attention to the biological parameters that may set a physical limit on the limit of detection for circulating tumor DNA (ctDNA)‐based liquid biopsy assays.